Differences in the Anthropometric and Physiological Profiles of Hungarian Male Rowers of Various Age Categories, Rankings and Career Lengths: Selection Problems - Alfőldi, Zoltan; Borysławski, Krzysztof; Ihasz, Ferenc; Soós, Imre; Podstawski, Robert (Frontiers in Physiology, 2021)
Background: Little is known about the anthropometric and physiological profiles of lower-ranking athletes who aspire to rise to the pinnacle of their profession. Aim: The aim of this study was to create anthropometric and physiological profiles of Hungarian male rowers of different age categories (15-16, 17-18, and over 18 years), sports rankings and career lengths. Materials and Methods: Anthropometric and physiological profiles were created for 55 juniors, 52 older juniors and 23 seniors representing seven of the largest Hungarian rowing clubs. One-way independent analysis of variance (ANOVA) was used to compare arithmetic means. Results: Rowers in older age categories were significantly taller (185.0±5.0 cm vs 183.0±7.3 cm vs 178.7±7.2 cm) and heavier (81.1±8.8 kg vs 73.7±8.4 kg vs 66.8±12.3 kg) than their younger peers, with significantly higher BMI values and larger body dimensions. Compared to younger athletes, rowers in older age categories also covered 2000 m significantly faster (6.6 ± 0.3 min vs 6.9 ± 0.4 min vs 7.5 ± 0.5 min) while developing significantly more power (372.2 ± 53.0 W vs 326.8 ± 54.5 W vs 250.6 ± 44.6 W). Similarly, seniors and older juniors had higher values of maximal oxygen uptake and force max (by 6.2 and 7.0 ml/kg/min, and by 263.4 and 169.8 N). Within the older juniors, internationally ranked rowers had significantly greater body height (+5.9 cm), body mass (+6.1 kg), sitting height (+2.7 cm), arm span (+7.9 cm), limb length (+3.73 cm) and body surface area (+0.21 m2). They also rowed 2000 m significantly faster (– 0.43 min, p < .001) and had significantly higher values of power (+58.3 W), relative power (+0.41 W/kg), jump height (+4.5 cm), speed max (+0.18 m/s) and force max (+163.22 N). Conclusions:. The study demonstrated that potential differences in anthropometric and physiological profiles are more difficult to capture in non-elite rowers, and that the final outcome may be determined by external factors. Therefore, athletes with superior aptitude for rowing are more difficult to select from among lower-ranking rowers, and further research is needed to determine specific training requirements to achieve the maximum rowing performance.